Genres of heritage authenticity. Denotations from a pilgrimage landscape - Andriotis, Konstantinos (My University, 2011)
Whilst several tourism scholars have deconstructed the notion of authenticity on heritage environments either from a theoretical or empirical perspective, few, if any, have undertaken a close look at Pine and Gilmore’s (2007) genres of authenticity, namely natural, original, exceptional, referential, and influential. It is the aim of this study to overcome past research negligence by rendering the appeal of the five genres of authenticity in the case of Mount Athos, a religious heritage, or in other words, pilgrimage landscape located in northern Greece, which can be considered as the last surviving byzantine complex of monasteries. Based on the findings of the study, this paper links the five genres of authenticity with past research on pilgrimage experience. Keywords: genres of authenticity, religious heritage experience, pilgrimage landscape, Christian orthodoxy.
Keywords: Christian orthodoxy; Genres of authenticity; Pilgrimage landscape; Religious heritage experience